LncRNA-UCA1 regulates lung adenocarcinoma progression through competitive binding to miR-383. Issue 2 (17th January 2023) - Tang, Li; Wang, Sheng; Wang, Yapeng; Li, Kang; Li, Qiang
ABSTRACT: The present study aimed to assess the role of the long non-coding RNA-urothelial cancer associated 1 (lncRNA-UCA1)/microRNA (miR)-383/vascular endothelial growth factor A (VEGFA) axis in regulating lung adenocarcinoma physiology through in vivo and in vitro experiments. The expression profile of lncRNA-UCA1 was analyzed by genome-wide analysis from GSE146459. The cell counting Kit-8, colony formation, wound healing and transwell assays were performed to evaluate the effects of lncRNA-UCA1 in vitro . In addition, luciferase reporter assays were performed to confirm the binding site. The expression levels of miR-383 and VEGFA in tumor cells were measured using reverse transcription-quantitative PCR. HCC-78 was also transfected with miR-383 mimics, inhibitors and siRNA-VEGFA before their viability was also assessed. Xenograft models were established in nude mice to investigate the tumor characteristics in vivo . The expression of lncRNA-UCA1 was significantly increased in tumor tissues and cells compared with adjacent tissues or HBE cells. Silencing lncRNA-UCA1 expression in cells resulted in a reduction in lung cancer cell viability. In addition, lncRNA-UCA1 silencing increased the expression of miR-383. Inhibiting miR-383 expression increased HCC-78 proliferation, migration and invasion, whilst reducing their apoptosis. miR-383 was shown to specifically target VEGFA to inhibit its expression at both the protein and mRNA levels. VEGFA knockdown resulted in a reduction in all aforementioned aspects of HCC-78 cell activity. In addition, inhibiting miR-383 expression led to larger tumor sizes in vivo . To conclude, the results of the study suggest that lncRNA-UCA1 can regulate the expression of miR-383 and, in turn, VEGFA. Graphical Abstract: uf0001